Prospects and Challenges of Micro Small Medium Enterprises (MSMEs) in India: A comparative Study (International Journal of Food and Nutritional Sciences, 2022)
SMEs are considered to be driving stone of any country’s economy be it under developed or developed as it provides maximum employment to locals and helps in raising the standard of living. In most developing countries, Micro, Small and Medium enterprises (MSMEs) constitute the bulk of the industrial base and contribute significantly to their exports as well as to their GDP or GNP (Kharbanda, V. P., 2001). SMEs are said to be the lifeblood of any vibrant economy and they are known to be the silent drivers of a nation’s economy (Monika, S., et. al., 2010). The majority of people living in rural area draw their livelihood from agriculture and allied sectors. However, the growth and balanced development of other sectors such as industries and services is also necessary to sustain the growth of Indian economy in an inclusive manner. It has proved to be very highly dynamic sector in Indian economy which not only plays an important role in providing employment opportunities to people but also facilitates in the growth and development in rural areas which provides many facilities to the people living in or around the industry. It proves to be cost beneficial for industrialists in developing economy as it requires less capital compared to large industries. It also plays prominent role in boosting production in country and gives a major base for self-reliance and domestic production. According to various researches and examples taken into consideration the major problems faced by SMEs in India and as a result affects the Indian Economy on a very large scale. Solutions to these problems can open many doors to revive the Indian Economy and improve the conditions.